A Crematorium Complex: Manhattan, Kansas - Robert Bahan; Laurie Carron; David Hecht; Matthew Masilionis; Rhonda Miller (Oz, 1986)
Today, a paucity of communicable design strategies or tactics exist for vitalizing the experiential and expressive relationship between built form and landscape. Landscape was not a primary concern of the Modern Movement except as a neutral green field upon which buildings were placed...